The results of the Regional competition of scientific and educational projects «Effective scientific library: ideas, approaches, decisions» - N. S. Redkina (Библиосфера, 2014)
The results of the competition of scientific and methodical projects that increase the work efficiency of scientific libraries developing their innovation activities, forming favorable public opinion about the innovative potential stimulating the activity of library are described.